A numerical study of blast resistance of fire damaged ultra-high performance concrete columns. (15th March 2023) - Xu, Zhenhuan; Li, Jun; Wu, Chengqing
Highlights: Blast resistance of UHPC column pre- and post-fire hazard was studied. Exposure to elevated temperature changed blast induced column failure mode. Bond-slip behaviour had varying impact on the blast resistance. Pressure-impulse diagrams were developed for fire damaged UHPC columns. Abstract: Concrete structures may experience fire and blast during their service life as a result of accidental explosions or vehicular collisions. Both fire and blast can cause severe damage that threatens the structural safety. In the present study, reinforced concrete columns fabricated by ultra-high performance concrete (UHPC) are investigated under coupled fire and blast loads. Strength degradation and damage of UHPC and steel reinforcement after exposure to elevated temperature (up to 800 °C) were established based on the experimental data. In addition to the detrimental effect on individual material, bond-slip behaviour between the UHPC and reinforcement affected by the elevated temperature was considered. The findings revealed that material strength degradation and damage owing to elevated temperature significantly influenced the structural blast resistance, and the degraded bond-slip behaviour had varying impact on the structural response depending on the structural damage mode. Up to 10% mid-span displacement differences were noted in columns with/without the consideration of bond-slip behaviour. Different failure mechanisms pre- and post-fire damage were observed in the numerical simulations. To quickly assess blast induced damage on UHPC columns, Pressure-Impulse (P-I) diagrams of the UHPC columns before and after elevated temperature were established and empirical formulae were proposed to generate the P-I diagrams.